1970
DOI: 10.31055/1851.2372.v49.n4.9897
|View full text |Cite
|
Sign up to set email alerts
|

Vegetación de afloramientos carbonáticos de montañas del centro de Argentina

Abstract: En las montañas del centro de Argentina, con una intensa fragmentación y reemplazos dela vegetación natural, los afloramientos rocosos constituyen hábitats importantes para la conservaciónde la biodiversidad, como refugios de especies endémicas y raras. En este trabajo se exploró lavariación composicional local de la vegetación en afloramientos de mármoles cálcicos y dolomíticosde las sierras de Córdoba y se compararon las asociaciones entre diferentes tipologías geoquímicas yla composición florística en un gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 2 publications
1
14
0
1
Order By: Relevance
“…Since FOR and FOV sites are all close together, and the distinction between FOR and FOV was confirmed by the presence of some indicator species, geological substrate may be the major factor for distinctiveness. A caveat of the present study is the small number of FOR sites, however, geological substrate has been identified as one of the major factors affecting the distribution of tree species in many forest communities (Aukema et al, 2007;Cantero et al, 2014;Pérez-García et al, 2009;Rivera et al, 2000;Sawada et al, 2015;Tang et al, 2011;Wiser & Buxton, 2009). Among Mexican tropical forests, floristic similarity has been related to geographical distances where close sites are more similar in floristic composition, but there are also nearby sites with greatly different floristic compositions, and because bioclimatic features were similar, this difference was attributed to geological substrate (Gallardo-Hernández et al, 2008;Pérez-García & Meave, 2004;Ruiz-Jiménez, Téllez-Valdés, & Luna-Vega, 2012).…”
Section: Elevation (M Asl)mentioning
confidence: 88%
See 1 more Smart Citation
“…Since FOR and FOV sites are all close together, and the distinction between FOR and FOV was confirmed by the presence of some indicator species, geological substrate may be the major factor for distinctiveness. A caveat of the present study is the small number of FOR sites, however, geological substrate has been identified as one of the major factors affecting the distribution of tree species in many forest communities (Aukema et al, 2007;Cantero et al, 2014;Pérez-García et al, 2009;Rivera et al, 2000;Sawada et al, 2015;Tang et al, 2011;Wiser & Buxton, 2009). Among Mexican tropical forests, floristic similarity has been related to geographical distances where close sites are more similar in floristic composition, but there are also nearby sites with greatly different floristic compositions, and because bioclimatic features were similar, this difference was attributed to geological substrate (Gallardo-Hernández et al, 2008;Pérez-García & Meave, 2004;Ruiz-Jiménez, Téllez-Valdés, & Luna-Vega, 2012).…”
Section: Elevation (M Asl)mentioning
confidence: 88%
“…Forest communities on rock outcrops have a distinctive floristic composition and physiognomy with respect to that of the surrounding forests. Outcrops with different substrates have been recognized worldwide as providing important habitats for biodiversity conservation, particularly for endemic and rare species (Aukema, Carlo, & Collazo, 2007;Cantero et al, 2014;Gallardo-Hernández, Velázquez, & Asbjornsen, 2008;Pérez-García & Meave, 2004;Pérez-García, Sevilha, Meave, & Scariot, 2009;Rivera, Zimmerman, & Aide, 2000;Wiser & Buxton, 2009). Some differential trends have also been reported in vegetation structure and species composition on outcrops compared to those of nearby forests on deeper soils (Brewer, Rejmánek, Webb, & Fine, 2003;Gallardo-Hernández et al, 2008;Sawada et al, 2015;Tang, Lü, Yin, & Qi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the southern hemisphere, the dolomite phenomenon or dolomitophily (according to Mota and colleagues [ 17 ]), has been noted in South Africa [ 7 , 26 , 46 ] and, to a lesser extent, in Australia and Tasmania [ 31 ]. There are also allusions to South America, although not very precise [ 47 ]. In Asia there are no excessively specific references, but it seems to occur in some mountains in eastern Anatolia, in the Irano-turanian region [ 48 ], and also in Tibet and Himalaya [ 49 , 50 , 51 ].…”
Section: The Extent Of the Dolomite Phenomenonmentioning
confidence: 99%
“…En ocasiones, esta especie nidifica en rocas accesibles para turistas y escaladores, lo cual puede llevar a que los huevos sean eventualmente abandonados o a que los individuos se acostumbren a la presencia de los seres humanos (Lambertucci and Speziale 2009). También se llevaron a cabo trabajos sobre la flora saxícola en el centro del país, en particular en zonas donde los afloramientos son muy aprovechados para la explotación minera y, en consecuencia, se están convirtiendo en sitios vulnerables, con demandas crecientes proyectadas a futuro (Cantero et al 2014(Cantero et al , 2017. Sin embargo, esta es una temática en la que hacen falta estudios con evaluaciones más generales en cuanto a los impactos que sufren las comunidades habitantes de los roquedales en distintas zonas del país y bajo diferentes impactos antrópicos.…”
Section: Disturbios Sobre Roquedalesunclassified